One-pot Synthesis of Indenonaphthopyrans Catalyzed by Copper(II) Triflate: A Comparative Study of Reflux and Ultrasound Methods - Turhan, Kadir; Ozturkcan, S. Arda; Uluer, Mehmet; Turgut, Zuhal (SLOVENSKO KEMIJSKO DRUSTVO, 2014)
An effective and environment-friendly protocol for the synthesis of indenonaphthopyrans has been developed by one-pot reaction of 2-naphthol, various aromatic aldehydes and 1,3-indandione, in the presence of copper(II) triflate as the catalyst while using reflux (Method A) and ultrasound (Method B). The Method B approach offers the advantages of a simple reaction method, short reaction time, excellent yield, and showcases the economic importance of the catalysts for such processes.
Keywords: Indenonaphthopyran; ultrasound; copper(II) triflate; 1,3-indandione; 2-naphthol; PROMOTED SYNTHESIS; IONIC LIQUIDS; BETA-NAPHTHOL; DERIVATIVES; CONDENSATION; CHLORIDE; ACID; Chemistry